Influence of landfill and land use scenario on runoff, evapotranspiration, and sediment yield over the Chinese Loess Plateau. (February 2021) - Huo, Aidi; Yang, Lei; Luo, Pingping; Cheng, Yuxiang; Peng, Jianbing; Nover, Daniel
Highlights: The mutual feedback mechanism between loess erosion and GCHP is analyzed. By changing the topography, we achieved the designed GCHP scenarios. To seek the best GCHP scheme in the basin, five scenario models were set up. Grass vegetation in the gully landfilled area is more sustainable for GCHP projects. Abstract: The Gully Consolidation and Highland Protection (GCHP) project was implemented across the Loess Plateau. Understanding the impacts of the GCHP requires applications of a distributed hydrologic model. The Soil and Water Assessment Tool (SWAT) and Geography Information System (GIS) were used for evaluating the GCHP project's impact on runoff and sediments in the catchment. The correlation coefficient value, the relative error and the Nash–Sutcliffe index are 0.83, –2.30% and 0.89 for the calibration period of our SWAT model in Yanwachuan (YWC) gully by using SWAT Calibration and Uncertainty Programs (SWAT-CUP) software. The distributed hydrological model was used to simulate five scenarios of a typical watershed YWC gully in Longdong Loess Plateau, and analyzed the response of runoff, sediment, and evapotranspiration under different designed scenarios of GCHP project. The results show that gully head landfill (the loess soil were directly transferred and dumped from other places) can reduce the runoff and sediment. The simulated annual average runoff is about 2.5% lower after landfill than that in the natural state, but the evapotranspiration is about 2.4% higher. The grassland plays a more important role in water conservation than forest vegetation in the YWC watershed. The results also show that the SWAT model is useful for the study of the hydrological response of GCHP at the watershed scale. The results of this study are providing scientific information to predict and prevent soil erosion.